A prospective study of 20 cases of maternal outcome in morbidly adherent placenta in tertiary care hospital - Vora, Krishna; Chandana, Pallavi; Patel, Amrita; Jain, Mahima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Morbidly adherent placenta with its variants is one of the most feared complication causing high morbidity and mortality in obstetrics. Aim of this study is to help in identifying high risk pregnancies, planning line of management of morbidly adherent placenta. The objective of the study wad to evaluate the risk factors, different modes of management, maternal outcome in case of morbidly adherent placenta. Methods: A prospective study for one year was done to describe the incidence, causes, treatment, complications, and maternal morbidity and mortality associated with morbidly adherent placenta. Results: A total of 20 cases of morbidly adherent placenta were studied over one-year span at our Institute. Most of the women with morbidly adherent placenta were in the age group of 26-30years (55%).The most common aetiology of morbidly adherent placenta was previous caesarean scar with placenta praevia (85%). In majority, placenta accreta found. Total abdominal hysterectomy done in 12 patient and subtotal hysterectomy in 6 cases. Trial haemostasis with uterine sparing in 2 cases out of which one case underwent total hysterectomy due to massive haemorrhage on same day. Associated Bladder repair in adherent placenta with invasion of bladder was needed in 10% cases. There was 1 maternal death noted in this study. Conclusions: Leading cause of morbidly adherent placenta is previous caesarean section with placenta praevia, high index of suspicion, early antenatal diagnosis, planned surgery at high care centre with multi-disciplinary expertise, anticipation of blood volume transfusion, Delivery of foetus without manipulating placenta are key steps to reduce morbidity and mortality in morbidly adherent placenta. The decision to perform hysterectomy and conservative management to be individualized. Timely decision is the key to get success in morbidly adherent placenta as in other obstetric emergencies.